Design and Development of Fuzzy-PID Controller for Four-Wheeled Mobile Robotic Stability: A Case Study on the Uphill Road - brian raafi'u; Purwadi Agus Darwito; Alex Taufiqurrahman Zain; Fitri Adi Iskandarianto; Ahmad Fauzan Adziima; Herry Sufyan Hadi; Sefi Novendra Patrialova; Rakmad Amrinsyah Badrul Alam (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Design intelligent control to maximize the performance of the Four-Wheeled Mobile Robot (FWMR) in case of uphill road problems. The variation of slope angle and load variation on the uphill road is applied to know the performance of the automatic control system on FWMR. The research is divided into three two covering, system identification, design system and simulation testing. The Rotary speed control system response with fuzzy-PID control method has a good performance by anticipating various tilt angle 5o. The system can through uphill with loads 11N with a steady time and fast travel time. The best travel time in the 5o tilt angle condition is 2 seconds with a 4m circuit length. This research concludes that fuzzy-PID control can be implemented and increase the dynamic response of the FWMR effectively on the uphill road problems.